If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -9x = 147 + -37x Solving 11 + -9x = 147 + -37x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '37x' to each side of the equation. 11 + -9x + 37x = 147 + -37x + 37x Combine like terms: -9x + 37x = 28x 11 + 28x = 147 + -37x + 37x Combine like terms: -37x + 37x = 0 11 + 28x = 147 + 0 11 + 28x = 147 Add '-11' to each side of the equation. 11 + -11 + 28x = 147 + -11 Combine like terms: 11 + -11 = 0 0 + 28x = 147 + -11 28x = 147 + -11 Combine like terms: 147 + -11 = 136 28x = 136 Divide each side by '28'. x = 4.857142857 Simplifying x = 4.857142857
| x/2=-14 | | 4x+5=-125-9x | | 7.95+1.50m=31.95 | | 2.4(n-1)=12 | | 34=2(x+12) | | 6x=10(8-x) | | 7.6x=10(8-x) | | -10x=-6x | | 106-3x=15x+22 | | 3(x-2)-5=-4x+7x-16 | | 48-6x=3x+19 | | x/3=6 | | 13-9x=95-23x | | 3x-6+(9x-[6(x+4)-9])=9(x+3) | | s/12+7=9 | | 3x=30+6x | | 5-3n=1 | | 115-6x=10x+19 | | 2n-7=45 | | =2x-x^2 | | n/4-8=10 | | 4x-4=11x-81 | | x-2=2x-men | | 60-3x=6x+21 | | 7x+14=10x+5 | | 2x-10=-2+18 | | 5x+8=53 | | 5x+40=60 | | (x+3)=x+10 | | 2n+9=-29 | | 2x+20=8x+2 | | 10x^2-3c-27= |